The Dyslipidemia and Inflammatory markers as the risk predictors for cardiovascular disease in newly diagnosed premenopausal hypothyroid women. : Screening of metabolic derangements in hypothyroidism - Balamurugan, Vaideki; Maradi, Ravindra; Joshi, Vivek; Belle, Vijetha Shenoy; Goud, BK Manjunatha (Journal of Medical Biochemistry, 2022)
Background: Hypothyroidism can predispose systolic and diastolic cardiac dysfunction, increased peripheral vascular resistance, endothelial dysfunction, altered coagulopathy, and dyslipidaemia resulting in atherosclerosis. Thyroid hormones can influence homocysteine metabolism by regulating the methylenetetrahydrofolate reductase (MTHR). So, this study aimed to compare the markers homocysteine, high sensitive C-reactive protein (hs-CRP), and Atherogenic Indices (AI) between newly diagnosed hypothyroid and euthyroid premenopausal women. Methods: 80 Female patients aged between 20 and 45 years were enrolled in this study and were equally divided into cases and controls group. Laboratory tests included: i) Serum T3, T4, TSH was measured using electrochemiluminescence, ii) lipid profile, homocysteine, and hs-CRP were measured for all the participants. Atherogenic indices: Castelli risk indices I&II, Atherogenic coefficient (AEC), and Atherogenic Index of Plasma (AIP) were calculated using formulas. A comparison between the study groups was made by using the Independent t-test and Mann-Whitney U test. p-value <0.05 was considered significant. Results: Atherogenic indices (p<0.001) and homocysteine (p=0.014) were significantly increased in hypothyroid women as compared to euthyroid. 38 % of hypothyroid women and 25 % of euthyroid women had hs-CRP >3 mg/L. Conclusion: Premenopausal women with hypothyroidism have a greater predisposition for cardiovascular disease compared to euthyroid